التكامل الحسي لذوي الاحتياجات الخاصة التوحد، وضعية إعاقة ذهنية، متلازمة داون - رزاق سالم, جبارية; بالصحراوي, آمنة (University of Eloued جامعة الوادي, 2023)
Study summary in English : This study aims to find out the extent of " sensory integration " in people with disabilities , this is based on the following hypotheses : general hypothesis : the required level of sensory integration in people with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . Here is the proposed Sub - hypothesis : 1 ) The required level of visual - motor integration in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . 2 ) The required level of figure - ground relationship awareness in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 3 ) The required level of objects placed in the area in children with disabilities in the psychopedagogical center for mentally handicapped children in Touggourt is confirmed . 4 ) The required level of shape copying in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 5 ) The required level of sensory stimuli position in children with disabilities in the psycho 6 pedagogical center for mentally handicapped children in Touggourt is confirmed . 6 ) The required level of fingers recognition in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . 7 ) The required level of writing on the palm of the hand in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed 8 )The required level of motor balance in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 9 ) The required level of body position simulation in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . The study relied on the clinical approach , the sample was based on ( 7 ) cases of children with special needs (3)from autism ,(2)from mental disability ,(2)from down syndrome sponsored by the psychological and pedagogical center . The findings were dependedon sensory integration module , the processing was carried by the statistical package for social sciences ( SPSS.20) .study results have been verified . Study summary in English : This study aims to find out the extent of " sensory integration " in people with disabilities , this is based on the following hypotheses : general hypothesis : the required level of sensory integration in people with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . Here is the proposed Sub - hypothesis : 1 ) The required level of visual - motor integration in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . 2 ) The required level of figure - ground relationship awareness in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 3 ) The required level of objects placed in the area in children with disabilities in the psychopedagogical center for mentally handicapped children in Touggourt is confirmed . 4 ) The required level of shape copying in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 5 ) The required level of sensory stimuli position in children with disabilities in the psycho 6 pedagogical center for mentally handicapped children in Touggourt is confirmed . 6 ) The required level of fingers recognition in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . 7 ) The required level of writing on the palm of the hand in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed 8 )The required level of motor balance in children with disabilities in the psycho - pedagogical center for mentally handicapped children in Touggourt is confirmed . 9 ) The required level of body position simulation in children with disabilities in the psycho pedagogical center for mentally handicapped children in Touggourt is confirmed . The study relied on the clinical approach , the sample was based on ( 7 ) cases of children with special needs (3)from autism ,(2)from mental disability ,(2)from down syndrome sponsored by the psychological and pedagogical center . The findings were dependedon sensory integration module , the processing was carried by the statistical package for social sciences ( SPSS.20) .study results have been verified .
"دراسة ميدانية على سبعة حالات بالمركز النفسي البيداغوجي للأطفال المعوقين ذهنيا عمر بن جلول بولاية توقرت "
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: التكامل الحسي، l'intégration sensorielle, sensory integration; ذوي الإحتياجات الخاصة، Avec besoins spéciaux, People with special needs